2008
DOI: 10.1021/jp805936n
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Study on the Effect of Surface Treatments on the Electric Characteristics of ZnO Nanowires

Abstract: Treatment of ZnO nanowires (NWs) using hydrogen peroxide with increasing concentration results in a continuous increase in the amount of -OH group at the surfaces of the NWs, which demonstrates different characteristics in the transport behaviors of the NWs. Combined with results from theoretical simulation and microphotoluminescence, the variation in the nanowire transport property is explained by the change of carrier density and mobility as induced by the surface treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 19 publications
1
11
0
Order By: Relevance
“…[32][33][34] The obtained defect concentrations under different oxygen partial pressures are all about 2.58 Â 10 17 cm À3 , comparable with other literature studies. 44,45 The electron concentrations under a nitrogen atmosphere are 2.57 Â 10 15 cm À3 and 2.56 Â 10 17 cm À3 at 300 K and 700 K, respectively, which are consistent with the assumption of weak ionization at low temperature and complete ionization at high temperature. The decreased electron concentration at 700 K with increased oxygen partial pressure may be caused by the filling of oxygen atoms into the oxygen vacancies with the absorption of O À , 11,38 which could be recovered in the cooling process.…”
Section: Isolating the Effects Of Oxygen And Heat In The Darksupporting
confidence: 75%
“…[32][33][34] The obtained defect concentrations under different oxygen partial pressures are all about 2.58 Â 10 17 cm À3 , comparable with other literature studies. 44,45 The electron concentrations under a nitrogen atmosphere are 2.57 Â 10 15 cm À3 and 2.56 Â 10 17 cm À3 at 300 K and 700 K, respectively, which are consistent with the assumption of weak ionization at low temperature and complete ionization at high temperature. The decreased electron concentration at 700 K with increased oxygen partial pressure may be caused by the filling of oxygen atoms into the oxygen vacancies with the absorption of O À , 11,38 which could be recovered in the cooling process.…”
Section: Isolating the Effects Of Oxygen And Heat In The Darksupporting
confidence: 75%
“…26,29 Assuming E F moves down to E D at 600 K which is close to the starting value of the high-temperature stage and the defects have mostly ionized from this temperature ( Figure S3, Supporting Information), N D is calculated to be 2.64 × 17 cm −3 based on eq 3, which is comparable with other works (on the order of 10 17 ∼10 18 cm −3 ). 28,30,31 Then the electron concentration at the low-temperature stage can be evaluated by the following equation, if weak ionization is supposed 19 is equal to 63, ≫0.5, which is consistent with the hypothetical condition for eq 4, so the assumption of weak ionization at the low-temperature stage is reasonable. From the above discussion in this section, we can conclude that the conduction electrons are mainly provided by the defect ionization with the ionization energy of 0.3 eV, from weak ionization at the low-temperature stage to almost complete ionization at the high-temperature stage.…”
Section: Resultsmentioning
confidence: 59%
“…According to the related works, the main donor in ZnO is oxygen vacancy, which has the ionization energy (Δ E D ) about 0.3 eV. From the basic knowledge of semiconductor physics, it could be found that the Fermi level ( E F ) moves down as the ionization goes on, and when E F is equal to E D about 1/3 of the defects have been ionized. Then the defect concentration ( N D ) can be evaluated by the following formula n = N normalC nobreak0em0.25em⁡ exp ( E C E F K B T ) = N normalC nobreak0em0.25em⁡ exp ( E C E D K B T ) = 1 3 N normalD where N C is equal to 1.92 × 10 15 T 3/2 cm –3 . , Assuming E F moves down to E D at 600 K which is close to the starting value of the high-temperature stage and the defects have mostly ionized from this temperature (Figure S3, Supporting Information), N D is calculated to be 2.64 × 17 cm –3 based on eq , which is comparable with other works (on the order of 10 17 ∼10 18 cm –3 ). ,, Then the electron concentration at the low-temperature stage can be evaluated by the following equation, if weak ionization is supposed n = true( N normalC N normalD 2 true) 1 / 2 …”
Section: Resultsmentioning
confidence: 99%
“…Of most interest is the O 1s spectrum as this can reveal details of oxygen associated with hydroxyls, water, surface lattice oxygen and organic molecules. To examine the measured changes the O 1s peak was fitted with two or three Gaussian-Lorentzian components [53,56] which accurately matched the envelope to the raw data.…”
Section: ≡ -Equationmentioning
confidence: 99%
“…[61] The oxygen plasma has the effect of reducing the number of oxygen vacancies and/or increasing Zn vacancies which reduce the carrier concentration near the surface increasing the sample resistivity as shown by the multi-probe transport measurements. [30,51,56,64,65] The O-S peak of the as-received sample originates from a combination and balance of adsorbed surface oxygen ions, H 2 O, hydroxyls and adventitious carbon/hydrocarbons molecules all competing for adsorption sites. The emission associated with hydroxyl groups, or O 2ions in oxygen deficient regions on the ZnO surface, is often considered to be at a BE of ~1 eV nearer to the O-Zn peak than adsorbed H 2 O, O 2and oxocarbons which are generally considered to create a peak at up to ~3 eV greater BE than the O-Zn.…”
Section: ≡ -Equationmentioning
confidence: 99%